Implementasi Inovasi Layanan Digital Sabdopalon (Sistem Administrasi Berita Data Deso dan Pelayanan Online) di Kabupaten Jombang - Dewi Nur Laila, Fitriana; Habibi, Muhammad Mujtaba (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2023)
E-government is an effort to create good government management, including the creation of a digital service innovation, namely Sabdopalon, in Jombang Regency to improve the quality of services in villages. This article aims to determine the implementation of digital service innovation in Sabdopalon village in realizing e-government as well as the obstacles in its implementation. To find out, qualitative research methods were used with a descriptive type and data collection techniques including observation, interviews, and documentation. The analysis in this research uses elements of e-government success according to the Harvard JFK School of Government, namely Support, Capability, and Value. The research results show that the implementation of e-government through Sabdopalon's digital service innovation has not been implemented well. Even though there are legal guarantees from the local government, the infrastructure is not yet supportive enough and outreach is not comprehensive enough. The relationship with human resource capacity is still not optimal, but the budget is sufficient. In terms of value, it is good, that the existence of Sabdopalon makes it easier for people to get services, especially village administration correspondence. Obstacles encountered include a lack of human resources who understand IT well, many people do not know about the existence of Sabdopalon, and the uneven distribution of the internet network. Based on this, the local village government needs to optimize the implementation of Sabdopalon services through comprehensive socialization and provision of supporting infrastructure, as well as equal distribution of the internet network. so that the benefits of Sabdopalon services can be felt widely by the community.